Molding the Fear: Representations of Fatherhood in Clay by Violent Men - Michal Lev; Israella Klein; Daniella Barzilay; Renana Salmon (Creative Arts in Education and Therapy, 2023)
This article presents an artistic inquiry among three students during an art-based research course in the art therapy master’s program at Ono Academy, Israel. Their collaboration focused on composing inquiry modes that could explore paternal representations of violent men that arise in artmaking with clay. Three fathers who took part in an abuse-prevention art therapy group, their group facilitator as a witness, and the three student-researchers participated in the project. The paper focuses on the research method that comprised artmaking with clay, a questionnaire, observations, and discussions. Two main themes arose within the study: coexisting contrasts and false perfection as well as a gained sense of success and assurance that could project onto their perceptions of parenting. The project highlights the significance of artmaking with clay as a research tool and as a potential prophylactic treatment for preventing domestic violence.